Hemoglobin Levels and Red Blood Cells Distribution Width Highlights Glioblastoma Patients Subgroup With Improved Median Overall Survival - Kaisman-Elbaz, Tehila; Elbaz, Yonatan; Merkin, Vladimir; Dym, Lianne; Noy, Ariel; Atar-Vardi, Maya; Bari, Romi; Turiel, Sivan; Alt, Adi; Zamed, Tali; Eskira, Yael; Lavrenkov, Konstantin; et al. (Frontiers in Oncology, 2020)
Glioblastoma multiforme (GBM) is known for its dismal prognosis, though its dependence on patients' readily available RBCs parameters is not fully established. In this work, 170 GBM patients, diagnosed and treated in Soroka University Medical Center (SUMC) over the last 12 years were retrospectively inspected for their survival dependency on pre-operative RBCs parameters. Besides KPS and tumor resection supplemented by oncological treatment, age under 70 (HR = 0.4, 95% CI 0.24–0.65, p = 0.00073), low hemoglobin level (HR = 1.79, 95% CI 1.06–2.99, p = 0.031), and Red Cell Distribution Width (RDW) < 14% (HR = 0.57, 95% CI 0.37–0.88, p = 0.018) were found to be prognostic of patients' overall survival in multivariate analysis, accounting for a false discovery rate of < 5% due to multiple hypothesis testing. According to these results, a stratification tree was made, from which a favorable route highlighted a subgroup of nearly 30% of the cohorts' patients whose median overall survival was 21.1 months (95% CI 16.2–27.2)—higher than the established chemo-radiation standard first-line treatment regimen overall median survival average of about 15 months. The beneficial or detrimental effect of RBCs parameters on GBM prognosis and its possible causes is discussed.